The Effectiveness Of Water-Filled Rubber Weir Management On Flood Mitigation Caused By Rain And “Rob” (Java Slang) In Demak District - Fatchur Roehman (International Conference on Coastal and Delta Areas, 2017)
In Indonesia, there are many sources of water. They can be ground water, rivers or seas which are certainly not easy to process these resources. Many problems have to be solved in processing these resources, such as flooding and "rob" problems in the Demak district. When dry season comes, how can we provide raw water and pure water for irrigation and other problems? One of the right solutions is to make a rubber weir that contains water. Normally, weir contains wind but this study tries to use different methods of filling weir by using water to make it easier and more practical in the treatment. Identifying problems such as alternative flood and rob handling is intended to unravel the problems in traffic congestion, submerged settlements and industrial estates, and analyzes the stability of the flow that occurs in the water-filled rubber weir model. The formulation of the problem with the model of water-filled rubber weir must be followed by the experimental system conducted in the Lab Faculty of Engineering UNISSULA Semarang. Therefore, the main problems studied in this research are the experiment of the waterfilled rubber weir, the hydraulic effectiveness of the water-filled rubber weir, and stability analysis of numerical models of the water-filled rubber weir. The purposes of this study are analyzing the hydraulic effectiveness of water-filled rubber weir with SOBEK application, analyzing the characteristics of the water-filled rubber weir to obtain a good weir material based on appropriate technology, and conducting a stability analysis of the flow occurring in the water-filled rubber weir model, prototype simulation of water-filled rubber weir. Keywords: Management effectiveness, Water-filled rubber weir, Flood and rob prevention